(3GdQMeI aj GdWH hGdMceIs - (3eMeO GdegOj Hf EHQGgje GdUHjQj Gdjefj GdgfOj,J (B815 (3g` s ((3eMeO Hf eMeO Hf eMeO GdOfOGf s)
(3ChdgG (B:s
(3eHJhQI GdChd hjHOC ajgG CKfGA GdHGH GdKGfi Hbhdg(B: (3YQa JQcjHI hbHVI, hCbhd hGddg JYGdi CYde HCf Chd eG Ndb Gddg JYGdi WHjYI GdMQGQI hCUdgG ef GdMQcI GdchfjI GdJi gi bOQI Gddg JYGdi s
(3BNQgG (B:s
(3hEf cGfJ GdYdI YXjeI oeRefI eKd GdLRGe adojYGhO GdoeSgd cd CSHhY eQI Ch aj GdTgQ eQJjf Ydi bOQ bhi GdTNU hVYag aEfg UMjM oeLQH hHGddg JYGdi GdJhajb s
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B100 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs